Hubungan Tingkat Pengetahuan Pasien dengan Minat Perawatan Saluran Akar Gigi di Poli Gigi RS Daerah Beriman Balikpapan 2023 - Yulistina Yulistina; Sultan Amin Yasin; Arsad Arsad; Rezki Dirman; Rahmah Rahmah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Root canal treatment is a treatment that cannot be completed in one visit. Therefore, it is very important for patients to comply in order to complete root canal treatment within a few visits. But the need for public knowledge about the importance of undergoing root canal treatment so that the tooth does not end with extraction. This study aims to determine the relationship between the level of patient knowledge and interest in root canal treatment at the dental clinic at the Beriman Balikpapan Hospital. The type of research used is analytic observational with a cross sectional design. The population in this study were all patients at the Dental Clinic at the Beriman Hospital, Balikpapan. The sampling technique uses Random Sampling in which a sample consists of a number of elements selected at random. Then analyze the dynamics of the correlation between patient knowledge and interest in root canal treatment at the dental polyclinic at the Beriman Hospital in Balikpapan in 2023. The results of this study showed that the majority of respondents were highly knowledgeable and very interested in performing root canal treatment at the Dental Clinic at the Beriman Balikpapan Hospital, namely as many as 52 people (65%). Data analysis was carried out using the Kendall's tau formula and obtained a significant value of 0.002 <0.05 so that it can be concluded that there is a relationship between the level of patient knowledge and interest in root canal treatment at the dental polyclinic at the Beriman Balikpapan Hospital 2023.